Review of Hydrogen Gas Sensors for Future Hydrogen Mobility Infrastructure - Jun-Seo Lee; 안진우; 배수강; 이승기 (한국진공학회, 2022)
The indiscriminate use of fossil fuels has adverse effects, such as environmental pollution and climate change. Therefore, there is growing interest in using hydrogen as an eco-friendly energy source. Among the diverse applications of hydrogen energy, hydrogen mobility has attracted considerable attention because it can compensate for the limitations of existing internal combustion engines and electricity-based mobility. To this end, relevant hydrogen-based infrastructure is being built in urban areas with rapid technological advancements. However, recent explosions of hydrogen charging stations in Norway and hydrogen storage tanks in South Korea have led to anxiety and the rejection of hydrogen application infrastructure. Therefore, to ensure the stability and safe operation of newly built infrastructure for hydrogen mobility in urban areas, an advanced system is required to improve existing technologies for hydrogen safety management. A hydrogen sensor is a front-line device for identifying initial hydrogen leaks and monitoring the status of hydrogen; thus, it is a building block for safety management systems. In this review, the operating principles and state-of-the-art hydrogen sensors are described by focusing on their suitability in hydrogen mobility applications based on the possibility of miniaturization and high hydrogen selectivity.